Nose controls on delta wings at supersonic speeds - Bolton Shaw, B. W. (College of Aeronautics, Cranfield, 1950)
Expressions are derived for lξ and a2 of nose ailerons and nose elevators on a delta wing, as depicted in Fig. 1, in supersonic flight. Nose and trailing edge controls on delta wings in supersonic flight are compared.